BETWEEN NIHILISM AND ANARCHISM (A PHILOSOPHICAL POEM BY GHERASIM LUCA) - Ştefan BOLEA (Studia Universitatis Babeș-Bolyai. Philosophia)
In this paper we provide a new solution to the nihilist dilemma of non-being's precedence over being. Starting from proponents of nihilism like Arthur Schopenhauer, Friedrich Nietzsche and Emil Cioran, we move to the anti-systemic "war machine" of Romanian-French poet Gherasim Luca, who, inspired by anarchistic theoreticians and Symbolist poets, asserted that only direct and concrete action could harass and sabotage the hegemonic power. His poem, Tragedies Which Are Meant To Happen is not only an important text of Romanian surrealist poetry, but also a page of the modern history of anarchistic philosophy.